Atlas of Multiparametric Prostate MRI With PI-RADS Approach and Anatomic-MRI-Pathological Correlation (Springer International Publishing, 2018)
This atlas provides a comprehensive, state of the art review of the use of multiparametric MRI (mpMRI) for the imaging of prostate cancer, covering aspects from diagnosis and loco-regional staging through to the role of the technique after treatment and follow-up. The book contains a wealth of high-resolution images, many of them in color, and displays the anatomical-MRI-pathological correlation whenever appropriate. Readers will find a helpful overview on the current standardized method for reading and reporting on mpMRI, the Prostate Imaging Reporting and Data System (PI-RADS), version 2. Dedicated chapters focus on differential diagnosis and imaging pitfalls, and the inclusion of helpful diagrams and algorithms will further assist in image interpretation, enabling readers to ease and improve their use of mpMRI. Edited and written by very experienced radiologists, pathologists, and urologists; the Atlas of Multiparametric Prostate MRI will serve as a unique source of clinically relevant information and an aid to disease management for radiologists, urologists, pathologists, radiotherapists, and oncologists.